Design and Practice of LKJ Driver Alarm Monitor System - 谢兴中; 徐盛火 (机车电传动)
Design background, idea and principle of LKJ driver alarm monitor system were summarized, and the hard/software design, assembling program, main function and applications were introduced. Comparison between the presented system and the specific alarm device of locomotive HXD3 etc was taken out. All this proved that the presented system had the advantages of flexible function, low cost, simple installing and maintenance convenience etc.